Beban Pembakaran Dimethyl Ether (DME) dan Liquefied Petroleum Gas (LPG) - Riesta Anggarani; Maymuchar Maymuchar; Cahyo S. Wibowo; I Made K. Dhiputra (Fakultas Teknik dan Teknologi - TANRI ABENG UNIVERSITY, 2019)
Dimethyl Ether has similar physical properties with LPG that made it potential to substitute LPG for fuel application. However, the DME calorific value of almost 40% lower than LPG affecting the combustion qualities of DME when considered to be used in current LPG combustion system. Investigation on the combustion performance of DME compared to LPG in diffusion burner is needed to know the parameters affecting the flame characteristics. This paper focus on the burning load characteristic comparison between DME and LPG in relation with burner nozzle diameter and flame height produced. The experiment was conducted using a barrel type burner where fuel is injected into combustion chamber of atmospheric pressure and the oxygen diffused from surrounded air. The barrel burner consists of the barrel and burner head which connected by screw connection. The nozzle hole placed in the top center of burner head. The nozzle diameter is varied in this experiment from 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm and 5.0 mm. At each diameter, the fuel is injected in various flow rate, and the resulted flame is measured for its flame height. We run two series of measurement, one for DME and one for LPG in the same condition. The burning load is calculated using mass flow rate, calorific value and nozzle diameter. The result show that DME burning load can reach similar burning load with LPG at lower diameter, where for DME reached at 3.0 mm – 4.0 mm, while for LPG reached at 4.0 mm – 5.0 mm. The flame height produced at similar burning load is significantly higher for LPG than DME. No effect of nozzle diameter and burning load on the produced flame height.